A randomized controlled trial of a six-session cognitive behavioral treatment of emotional disorders in adolescents 14–17 years old in child and adolescent mental health services (CAMHS) - Lorentzen, Veronica (BMC Psychol, 2020)
BACKGROUND: This study aims to investigate effectiveness of a 6-week, transdiagnostic cognitive behavioral therapy (CBT) for anxiety and depression in adolescents, the Structured Material for Therapy (SMART), in naturalistic settings of child and adolescent mental health outpatient services (CAMHS). METHODS: A randomized controlled trial with waiting list control (WLC) was performed at three community CAMHS in Norway. Referred adolescents (N = 163, age = 15.72, 90.3% girls) scoring 6 or more on the emotional disorders subscale of the Strengths and Difficulties Questionnaire (SDQ) were randomly assigned to SMART or to WLC. RESULTS: In the treatment group (CBT), 32.9% improved in the main outcome measure (SDQ), compared to 11.6% in the WLC. Clinically significant and reliable change was experienced by 17.7% in the CBT condition, compared to 5.8% in the WLC. No patients deteriorated. Statistically significant treatment effects were achieved for internalization symptoms, anxiety symptoms and general functioning. CONCLUSIONS: These promising findings indicate that SMART may be considered as a first step in a stepped care model for anxiety and/or depression treatment in CAMHS. The recovery rates imply that further investigations into the effectiveness of brief treatments should be made. Furthermore, there is a need for more comprehensive second-stage treatments for some of these patients. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02150265. First registered May 292,014.